A survey of Russian organisations - Kakabadse, Andrew P.; Kakabadse, Nada K.; Myers, Andrew (Cranfield University School of Management, 2009)
Fifty members from the Russian Managers Association completed a survey that explored views on Chairman of the Board and other aspects of Board performance. Although the number responding is small, the findings present some useful insights into Board performance within Russia.